EFFECT OF DESIGN CHANGING OF RING CLASP ON ITS RETENTIVE FORCE: EFEK PERUBAHAN DESAIN RING CLASP TERHADAP KEKUATAN RETENSI - Laith Mahmoud Abdulhadi,; Bilal Diab Saad Asoudi, (Dentika: Dental Journal, 2010)
Different designs of ring clasp were indicated in short or long span bounded saddle. However, few researches have been done to calculate their retentive absolute forces. The purpose of this in-vitro study was to measure the retentive force of four different ring clasp designs. A test model was made from maxillary plastic replica. Second molar was seated in silicone mould then poured with dental stone. 24 cobalt-chromium ring clasp designs were fabricated to engage 0.5mm undercut using standard casting technique. They were examined radiographically for any casting defects. The dislodging force was measured for each clasp using universal testing machine. The results showed that ring clasp design 2 produced the highest retentive force, while, clasp 4 was the lowest among the other clasps. In addition, significant difference regarding the mean retentive force was estimated among designs 1, 2 and 4. The means of retentive force of ring 1, 2, 3, and 4 were equal to 17.40 ±2.97, 17.52 ±3.05, 12.35±0 .98, and 11.15±2.15 N, respectively. Modifying the ring clasp design by adding extra rest or fortification will change its retentive force using the same undercut depth. Each ring design provides definite retentive force. As conclusion, each ring clasps design offered specific retentive force in dry environ-ment. However design 2 presented the highest force rate while design 4 was the least retentive.